2019
DOI: 10.1109/access.2019.2944877
|View full text |Cite
|
Sign up to set email alerts
|

A Gravitational-Double Layer Extreme Learning Machine and its Application in Powerlifting Analysis

Abstract: Powerlifting is a strength sport that is quite popular in the world. Powerlifters have their power levels varied at different ages and body weights, and their power levels are closely related to their performance. Therefore, studying the impact of age and weight on the performance of powerlifters is an important work. The traditional method relies mainly on artificial experience to judge the performance, and often does not get the desired results. In recent years, machine learning has developed rapidly, and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…The planning phase research was related to creating training (exercise) plannin g (e.g., [55][56][57]61,106,126]), nutrition planning (e.g., [55,151]), and full framework approaches (e.g., [78,131,145]), which were related to all training phases. Identifying (2.RQ ) the most SST supported sports research was presented previously on the Figure 5, where it was shown that the most research was done in the domains of soccer (12 papers • [78-89]), running (11 papers • [64-74]), and weight lifting (9 papers • [110][111][112][113][114][115][116][117][118]).…”
Section: Discussionmentioning
confidence: 99%
“…The planning phase research was related to creating training (exercise) plannin g (e.g., [55][56][57]61,106,126]), nutrition planning (e.g., [55,151]), and full framework approaches (e.g., [78,131,145]), which were related to all training phases. Identifying (2.RQ ) the most SST supported sports research was presented previously on the Figure 5, where it was shown that the most research was done in the domains of soccer (12 papers • [78-89]), running (11 papers • [64-74]), and weight lifting (9 papers • [110][111][112][113][114][115][116][117][118]).…”
Section: Discussionmentioning
confidence: 99%
“…These can be obtained from the previous layers without any transformations. 17,[38][39][40][41][42] No iterations are performed in the whole process of the ELM technique and it is completed through a single mathematical change. Apart from this, the solution of the least square technique in ELM is very fast when compared with Quadratic SVM.…”
Section: Classification Of Retinal Images Using Elmmentioning
confidence: 99%
“…-Контроль -відсутні дослідження щодо фітнесу в тренажерних залах, айкідо, стрільби з лука, метання молота, стрибків на лижах та йоги. Важка атлетика Реальні [113] [114], [115] Катання на лижах Реальні [116] Приватний -Синтетичні [97] Приватний -Реальні [88], [117], [118], [119], [120], [121], [122], [123], [124], [125], [126], [127], [128], [129] Вільні, відкриті наборів даних із домену SST та спортивного «скаутингу» існують, наприклад, [130], [131], [132], [133], [134], [135], [136]).…”
Section: видобування данихunclassified